Nasopharyngeal ACE2, CD147, and TMPRSS2 expressions in MIS-C patients (Annals of Medical Research, 2024)
Aim: Multisystem Inflammatory Syndrome in Children (MIS-C) is a disease developed after about eight weeks of the new coronavirus disease (COVID-19) infection in children. The underlying reason for MIS-C is still unknown. This study aims to assess the nasopharyngeal expressions of Angiotensin-converting enzyme 2 (ACE2), the differentiation 147 receptor cluster (CD147), and the transmembrane serine protease 2 (TMPRSS2) receptors in the MIS-C population. Since these receptors are related to COVID-19 infection, children with previous COVID-19 history were included as a control group. This study is essential for future studies to see if there is any significant expression difference between these receptors in control and MIS-C populations.Materials and Methods: The prospective cohort study took place at Ondokuz Mayıs University. The participants of this study consisted of patients aged 0-18 years who were diagnosed with MIS-C due to COVID-19 infection or patients with only previous COVID-19 pneumonia but without MIS-C development. A total of 79 cases were registered in this study. Nasopharyngeal samples of children were collected. Total RNA was isolated from all samples. The expression of ACE2, CD147, and TMPRSS2 genes was accessed by real-time quantitative PCR (RT-qPCR).Results: Nasopharyngeal expression of CD147 and TMPRSS2 were not changed in COVID-19 (n=42) and MIS-C (n=37) cases.  Expression of ACE2 was increased in the under 10-year-old MIS-C group (n=23) (p=0.004381).Conclusion: Future studies may exclude the nasopharyngeal expression of CD147 and TMPRSS2 to develop MIS-C. Further investigations are required to learn how ACE2 expression contributes to MIS-C development.
Keywords: ACE2; CD147; COVID-19; MIS-C; TMPRSS2